2011
DOI: 10.1007/s11367-011-0283-9
|View full text |Cite
|
Sign up to set email alerts
|

How does co-product handling affect the carbon footprint of milk? Case study of milk production in New Zealand and Sweden

Abstract: Purpose This paper investigates different methodologies of handling co-products in life cycle assessment (LCA) or carbon footprint (CF) studies. Co-product handling can have a significant effect on final LCA/CF results, and although there are guidelines on the preferred order for different methods for handling co-products, no agreed understanding on applicable methods is available. In the present study, the greenhouse gases (GHG) associated with the production of 1 kg of energy-corrected milk (ECM) at farm gat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
69
1
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 128 publications
(76 citation statements)
references
References 11 publications
5
69
1
1
Order By: Relevance
“…LCA has advantages over IOA in the embodied carbon evaluation of single products because it collects production information from the technical details [23][24][25][26][27][28][29], but it shows shortcomings in the carbon calculation of an area, which needs massive data support and truncation errors [30]. So recent studies that focus on all sectoral products mostly use IOA to calculate the regional and national carbon footprints.…”
Section: Introductionmentioning
confidence: 99%
“…LCA has advantages over IOA in the embodied carbon evaluation of single products because it collects production information from the technical details [23][24][25][26][27][28][29], but it shows shortcomings in the carbon calculation of an area, which needs massive data support and truncation errors [30]. So recent studies that focus on all sectoral products mostly use IOA to calculate the regional and national carbon footprints.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, while research on the use of LCA for dairy (Flysjö et al 2011;Thomassen et al 2009;van der Werf et al 2009) and beef production (Lieffering et al 2010;Nguyen et al 2012;Peters et al 2010;Wiedemann et al 2015a;Williams et al 2006) has been reported for several major production regions of the world, there are fewer published LCAs on sheep and most of these have focussed on lamb production. Lamb LCA studies cover production in a range of regions, notably the Mediterranean (RipollBosch et al 2013), New Zealand (NZ) (Gac et al 2012;Ledgard et al 2011), the United Kingdom (UK) (EdwardsJones et al 2009;Williams et al 2006) and Australia (Peters et al 2010;Wiedemann et al 2015b). Only two published studies have specifically investigated the LCA of wool, with both examining meat and wool production from single-casestudy farms in Australia (Brock et al 2013;Eady et al 2012).…”
mentioning
confidence: 99%
“…On the other hand, higher milk yields result in fewer dairy cows and, therefore, beef cows are required to produce a certain amount of meat. So-called allocations (Cederberg and Stadig, 2003;Feitz et al, 2007;Thomassen et al, 2008;Flysjö et al, 2011;Zehetmeier et al, 2011) are necessary to assess CFs for milk and beef production. For example, Zehetmeier et al (2011) made such an economic allocation of GHG-emissions in dairy husbandry (milk and beef) on the basis of 6 000; 8 000 or 10 000 kg milk per cow per year and asked for the same amount of beef with increased milk yields.…”
Section: Ruminants In the Food Chainmentioning
confidence: 99%